Spotlight on ORNAC Members - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2014)
Pat Pocock is a Registered Nurse who has worked in the perioperative field for fifty years. She started her career as a Perioperative Registered Nurse at the Grace Hospital in Windsor, ON, followed by a year working in the Operating Room at the University of Alberta Hospital in Edmonton. The next 14 years were spent in leadership and teaching roles in Windsor. The last 28 years of her hospital career were spent in leadership roles at St Joseph’s Hospital in London, ON. Pat is past Co-Chair of the Canadian Operating Room Leaders (CORL) network and has committed her career to issues related to leadership within perioperative nursing.